Durace a imunizace portfolia z obligací - Prouza, Ludvík (Univerzita Pardubice, 1998)
In this article, the notion of bonds duration is investigated its significance for bonds portfolio imunization is shown.
Keywords: obligace; portfolio; durace; imunizace